Teaching Evolution in Muslim Countries: Is Constructivism a Solution or a Threat? - Özgür Taşkın (Yaşadıkça Eğitim, 2020)
Since the turn of this century, constructivism has dramatically influenced science education and, particularly in Muslim countries, the teaching of evolution. This influence came about gradually. After the 1980’s, Muslim graduate students studying Education in Western universities have been taught constructivism both as a theory of learning and a philosophy, more specifically, as an epistemological theory. This has impacted these students’ views of the nature of science, scientific argumentation, multiculturalism, and the function of democratic values and practices in education. The scope of this influence raises a number of serious questions: Has constructivism introduced a mode of reasoning into science and science education that is foreign to, and even anathema to, scientific discourse? Why does almost every science education research paper suggest or imply negotiation with clergy and religious NGOs? Such questions are discussed in the present paper. To answer these questions, this paper examines in the context of Enlightenment and secularism theoretical frameworks, the methodologies, and suggestions regarding the teaching of evolution in Muslim countries.